Pengembangan Media Komik Foto untuk Meningkatkan Keterampilan Menulis Narasi Peserta Didik Sekolah Dasar - Priatiningsih, Endah; Widosari, Ani; Juhana, Juhana (Institut Agama Islam Negeri Palopo, 2022)
The state of Indonesia has a writing skill level of about 84% of the total population, but only 12 books are published for one million Indonesians per year, which ranks 60 below Thailand out of 61 countries in the overall world ranking. Purbalingga Regency itself, on the portal page of the Communication and Informatics Service, stated that around 4% or 6000 people in Purbalingga cannot read and write. The illiterate community places Purbalingga in 26th out of 35 districts in Central Java. Students at the time of learning to write narratives still tend to be passive, and less focused, even teachers still useless interesting methods. The teaching and learning process has not used appropriate techniques, methods, and learning models. Based on the results of interviews with 15 students in the Sultan Agung cluster, Karanganyar district, it was found that out of 20 students, 15 children liked comics. The research objective is to develop and produce narrative writing instructional media for elementary school students. The research method is interview, observation, and document with 3 stages: preliminary study, model development, dan model test. The results showed that the condition of learning narrative writing skills for elementary school students was still not optimal and based on the t-test the use of photo comic media products proved effective to improve the narrative writing skills of fifth-grade elementary school students.